Implementation and Consistency Issues in Distributed Shared Memory - Das, Debendranath; Saptarshi Ray, Ryan; Kumar Ray, Utpal (International Journal of Computer Sciences and Engineering, 2025)
Presently all programmers want to perform their tasks much faster than before. So, Parallel Processing comes into the picture to satisfy the increasing demands. Till a long time, parallel programs were only written either for multiprocessing environment or multi-computing environment. However, both of these parallel processing systems have some relative advantages and disadvantages. Distributed Shared Memory (DSM) system is a new and attractive area of research which combines the advantages of both shared-memory parallel processors (multiprocessors) and distributed systems (multi-computers). However, in DSM environment there are some critical issues like memory consistency that should be handled carefully. In this paper, an overview of DSM is given after a brief description of Distributed Computing Systems. Later various implementation issues and consistency models related to DSM are shown. Then an example of a simple program is given that can be implemented in DSM environment using Open SHMEM.